A Concise Total Synthesis of (−)‐Berkelic Acid - Cheng, Hong‐Gang; Yang, Zhenjie; Chen, Ruiming; Cao, Liming; Tong, Wen‐Yan; Wei, Qiang; Wang, Qingqing; Wu, Chenggui; Qu, Shuanglin; Zhou, Qianghui (Angewandte Chemie International Edition, 2021)
Reported here is a concise total synthesis of (−)‐berkelic acid in eight linear steps. This synthesis features a Catellani reaction/oxa‐Michael cascade for the construction of the isochroman scaffold, a one‐pot deprotection/spiroacetalization operation for the formation of the tetracyclic core structure, and a late‐stage Ni‐catalyzed reductive coupling for the introduction of the lateral chain. Notably, four stereocenters are established from a single existing chiral center with excellent stereocontrol during the deprotection/spiroacetalization process. Stereocontrol of the intriguing deprotection/spiroacetalization process is supported by DFT calculations. A concise total synthesis of (−)‐berkelic acid in eight linear steps was developed. This synthesis features a Catellani reaction/oxa‐Michael cascade for the construction of the isochroman scaffold, a one‐pot deprotection/spiroacetalization operation for the formation of tetracyclic core structure, and a late‐stage Ni‐catalyzed reductive coupling for the introduction of the lateral chain.